A regional approach for the development of TVET systems in the light of the 4th industrial revolution: the regional association of vocational and technical education in Asia. (5th July 2019) - Schröder, Thomas
ABSTRACT: This article discusses changes in the labor market in reference to industrial development and outlines perspectives for a set of competencies as an overall objective for technical and vocational education and training (TVET). Essential steps toward achieving this objective include a praxis-oriented approach in vocational didactics and its alignment with outcome-oriented qualification frameworks. Research on TVET is a driver for systemic development, thus supporting the process of adaptation and innovation of TVET systems. Especially, participatory action-research approaches encourage sustainable societal innovation, and generation of knowledge. The exchange of relevant knowledge is enhanced by international cooperation of the scientific community. The Regional Association of Vocational and Technical Education in Asia (RAVTE), as a network in East and Southeast Asia, is enhancing the development of TVET systems in the ASEAN region by supporting the establishment of vocational education as a scientific discipline, the education of vocational teachers, and through generation and dissemination of knowledge that can be applied by practitioners, administrators, and politicians.